2019
DOI: 10.1177/2058739219835106
|View full text |Cite
|
Sign up to set email alerts
|

Predicting value of neutrophil–lymphocyte ratio and CURB-65 score for early clinical stability of adult community-acquired pneumonia

Abstract: Early clinical stability has been proven to be vital for the treatment of community-acquired pneumonia (CAP). This research retrospectively analyzed the predictive implication of neutrophil-lymphocyte ratio (NLR) and confusion, urea >7 mmol/L, respiratory rate ⩾30 breaths/min, low blood pressure, and age ⩾65 years (CURB-65) score to predict early clinical stability of the adult CAP. Clinical data, CURB-65 scores, pneumonia severity index (PSI) scores, NLR on admission (within 24 h) of 230 patients between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
1
1
Order By: Relevance
“…Studies have shown that neutrophil-lymphocyte ratio, lymphocyte-monocyte ratio and platelet-lymphocyte ratio can also help to predict outcome in CAP. 23,24 But in our study no such consistent findings were observed. Though total leucocyte count and neutrophils were significantly raised in those with unfavorable outcome, their ratio was not statistically significant in our study, probably due to the proportionate rise of both the parameters.…”
Section: Resultscontrasting
confidence: 73%
“…Studies have shown that neutrophil-lymphocyte ratio, lymphocyte-monocyte ratio and platelet-lymphocyte ratio can also help to predict outcome in CAP. 23,24 But in our study no such consistent findings were observed. Though total leucocyte count and neutrophils were significantly raised in those with unfavorable outcome, their ratio was not statistically significant in our study, probably due to the proportionate rise of both the parameters.…”
Section: Resultscontrasting
confidence: 73%
“…15 Pada populasi dewasa, skor CURB-65 dan NLR berkaitan dengan resiko instabilitas klinis setelah 72 jam pasca inisiasi terapi. 16 Kombinasi CURB-65*NLR (cut off 9,06) merupakan prediktor paling signifikan dalam menentukan resiko mortalitas pada geriatric dengan pneumonia. 17 Pada pasien kami, menilik dari skor CURB-65 dan NLR yang tinggi (prediktor instabilitas klinis awal dan resiko kematian tinggi) sehingga perawatan pasien dilakukan ICU dan tidak di rawat bangsal biasa.…”
Section: Diskusiunclassified